Elastoplastic hybrid finite elements in the analysis of shear walls - Teguh, Moohamad
A special finite element technique for plane problem is presented with rotational and translational displacements at the nodes. The finite element system involves either solid shear walls or coupling beams connected to shear walls in the state of plane stress. A 12 degree-of-freedom rectangular hybrid finite element is developed. It is based on the principle of minimum complementary energy employing assumed-stress distribution. The present assumed-stress model deals with the initial-stress approach for elastoplastic analysis of shear walls under static loading. This approach leads to a set of simultaneous linear algebraic incremental equivalent equations to be accounted for at each step of loading. The unchanged elastic stiffness matrix is used throughout the loading process and the effects of plasticity are included as equivalent element loads. A numerical implementation was also provided as a representation of elastoplastic program.